3=3(2x-4)-3(4x+4)-10

Simple and best practice solution for 3=3(2x-4)-3(4x+4)-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3=3(2x-4)-3(4x+4)-10 equation:


Simplifying
3 = 3(2x + -4) + -3(4x + 4) + -10

Reorder the terms:
3 = 3(-4 + 2x) + -3(4x + 4) + -10
3 = (-4 * 3 + 2x * 3) + -3(4x + 4) + -10
3 = (-12 + 6x) + -3(4x + 4) + -10

Reorder the terms:
3 = -12 + 6x + -3(4 + 4x) + -10
3 = -12 + 6x + (4 * -3 + 4x * -3) + -10
3 = -12 + 6x + (-12 + -12x) + -10

Reorder the terms:
3 = -12 + -12 + -10 + 6x + -12x

Combine like terms: -12 + -12 = -24
3 = -24 + -10 + 6x + -12x

Combine like terms: -24 + -10 = -34
3 = -34 + 6x + -12x

Combine like terms: 6x + -12x = -6x
3 = -34 + -6x

Solving
3 = -34 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
3 + 6x = -34 + -6x + 6x

Combine like terms: -6x + 6x = 0
3 + 6x = -34 + 0
3 + 6x = -34

Add '-3' to each side of the equation.
3 + -3 + 6x = -34 + -3

Combine like terms: 3 + -3 = 0
0 + 6x = -34 + -3
6x = -34 + -3

Combine like terms: -34 + -3 = -37
6x = -37

Divide each side by '6'.
x = -6.166666667

Simplifying
x = -6.166666667

See similar equations:

| 36r^2-121= | | ln(6)+ln(x)=ln(6x) | | 42a^2+a-30=0 | | 6a^2-28a+16= | | 28/5 | | 36=b(5)(6) | | (B/9)-.5=(5/18) | | (x)(-3)-4=-10 | | 81x+36x+20=0 | | (3x^-5/8y^-7)^-2 | | 0=20t-5(t^2)+25 | | 4x-3/8 | | 6x-2x+7=x-2+9 | | 5x+6=30+x | | 30xm+15xn-20ym-10yn= | | 25x^4-81y^2=0 | | 1/4x=x-33 | | 5-(-3)+6= | | f(x)=-4x^2+16x-5 | | x/(36x^2-9) | | x+2x+5x=32 | | x^2+14xy+24y=0 | | 5+4ln(x)=7 | | x/36x^2-9 | | m^2+22m-4=0 | | y^4-6y^3+12y^2-10y+3= | | a=-1e+-1s+-1y | | w^2-13w+42.25=0 | | 1/4x^4-9/25=0 | | ydx=x(lnx-lny)dy | | 5x=(3x-3)(m+4) | | 0.90n=n+15 |

Equations solver categories